2015
DOI: 10.1136/bjsports-2014-094365
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in national Olympic level judo athletes: an epidemiological study

Abstract: Many body regions are prone to injury in the elite judo population. Women, especially those in the heavyweight classification, were more prone to severe injuries. Lightweights experienced more injuries than heavyweights among male athletes. Specifically, further studies are needed to confirm these findings and to address the impact of rapid weight loss practices on injury risk to implement effective preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 33 publications
1
50
1
3
Order By: Relevance
“…In a prospective study of elite Korean judo athletes, Kim et al found a similar pattern, with 32% of injuries to the upper and 39% to the lower extremity 22. Their finding of a higher proportion of injuries to the lower extremity might be due to differing definitions of injuries.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a prospective study of elite Korean judo athletes, Kim et al found a similar pattern, with 32% of injuries to the upper and 39% to the lower extremity 22. Their finding of a higher proportion of injuries to the lower extremity might be due to differing definitions of injuries.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have also reported injuries and overuse syndromes of the back. Kim et al reported that 17% of injuries dealt with the thoracic back/upper spine and the lumbar spine/lower back 22. Okada et al reported a prevalence of unspecific low back pain in 35% and radiologically abnormal findings in 82% of a group of Japanese college judo athletes.…”
Section: Discussionmentioning
confidence: 99%
“…There was one judo,24 three boxing,25–27 two taekwondo28 29 and two wrestling studies 30 31. There was also one multisport study that encompassed all four sports 32.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, the studies reported an assortment of statistical methods, with logistic regression analysis,24 Student’s t-test32 and χ 2  tests24 25 27 29 32 being the most common. Descriptive statistics such as proportions were reported in four studies26 28–30 that also reported injury incidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation